Chemical Engineer George L. Standart – between Science and Ideology - Věra Dvořáčková (Substantia)
George L. Standart was one of the few western scientists who decided to emigrate to communist Czechoslovakia. He was driven to do that by his leftist mindset, his conviction that there lay a more just and peaceful world behind the Iron Curtain, and also the feeling that he was at risk in his homeland, unsettled by McCarthyism. Although he was recruited as an informer first by the Soviet, and subsequently also the Czech intelligence services, they never found his work satisfactory as an agent, a situation exacerbated by his increasing academic workload. Most of all, George L. Standart was an outstanding scientist, one of the best in his discipline and at that time, who made an unexpected and unprecedented contribution to the Czechoslovak chemical sciences and their practical industrial applications.